Lower urinary tract symptoms in adolescent girls: a questionnaire-based study. (March 2021) - Serdinšek, Tamara; Sobočan, Monika; But, Špela; Špilak-Gomboc, Martina; But, Igor
Abstract: Objective: To determine the prevalence of lower urinary tract symptoms (LUTS) in female adolescent population. Study design: We performed a questionnaire-based study in nine randomly selected high schools in our country. Our primary aim was to evaluate the prevalence of certain LUTS in adolescent girls: frequency, urgency, nocturia, feeling of incomplete bladder emptying, dysuria, and urinary incontinence. The secondary aim was to investigate the effect of some possible risk factors on LUTS prevalence. Statistical analysis was performed using SPSS Statistics Programme. Descriptive statistics were calculated. Non-parametric test was used for comparison of numerical and Pearson's Chi-square test for categorical data. Logistic regression was performed to identify the independent prognosticators for LUTS presence. Statistical significance was set at p < 0.05. Results: We included 2745 adolescent girls. Their average age was 16.8 ± 1.2 years and 17.8 % of them regularly experienced at least one LUTS. The frequency of occasional LUTS was even higher. The most common symptom was urinary incontinence (5.9 %), followed by frequency (5.1 %), feeling of incomplete bladder emptying (4.8 %), urgency (3.1 %), and nocturia (2.6 %). Risk factors for LUTS presence were girls' school success, frequent pelvic pain, previous cystitis, history of night enuresis in childhood, and sexual intercourses in the last three months. Conclusions: According to our results, the prevalence of LUTS amongst female adolescents is high and can be associated with certain risk factors. In our opinion, further research should be directed into determining the effect of LUTS on adolescents' quality of life.